Pengaruh Pengetahuan Investasi, Financial Technology dan Efikasi Keuangan Terhadap Minat Mahasiswa Akuntansi Berinvestasi di Pasar Modal - Situmorang, Siony Veronika; L. Tobing, Vargo Christian (SCIENTIA JOURNAL, 2024)
Interest in investing is an encouragement to engage in investment activities with the aim of generating future profits. This study was conducted with the aim of knowing the effect, investment knowledge, financial technology and financial efficacy on accounting students' interest in investing in the capital market. The total population was 1.234 students and the sample in this study was 93 students. Using simple random sampling technique and primary data sources obtained by distributing questionnaires online using google form. Data processing using SPSS (Statistical Package for Social Science) software version 26. Data analysis techniques use validation tests and reliability tests, classical assumption tests to hypothesis testing. The results of hypothesis testing research (t test) investment knowledge partially has no significant effect, financial technology and financial efficacy partially have a significant effect on accounting students' interest in investing in the capital market. Simultaneous test research results (Test f) Investment knowledge variables, financial technology and financial efficacy simultaneously have a significant effect on accounting students' interest in investing in the capital market. The variable of investment knowledge, financial technology and financial efficacy on investment interest has a percentage of 67.9% with the remaining percentage, namely 32.1%, being influenced by other variables.